Monoclonal antibodies that distinguish Trypanosoma congolense, Trypanosoma vivax and Trypanosoma brucei - Nantulya, V.M.; Musoke, A.J.; Rurangirwa, F.R.; Saigar, N.; Minja, S.H. (Wiley, 1987)
Summary Monoclonal antibodies (MoAbs) were derived against in‐vitro‐propagated procyclic forms of Trypanosoma congolense, T. vivax, T. brucei brucei and T. b. rhodesiense in order to identify antigens for use in immunodiagnosis of African trypanosomiasis. The antibodies have been tested against procyclic and bloodstream form trypanosomes of 13 T. congolense, six T. vivax six T. b. brucei, four T. b. rhodesiense, five T. b. gambiense and three T. simiae isolates from different geographical areas by indirect immunofluorescent antibody test (IFAT) and enzyme‐linked immunosorbent assay (ELISA). The MoAbs raised against T. b. brucei reacted with all the brucei group of trypanosomes but not with T. congolense, T. simiae or T. vivax. Likewise, MoAbs against T. congolense reacted with T. congolense and T. simiae but not with any of the other species, while those against T. vivax reacted with T. vivax only. The antigens recognized by these MoAbs were present in lysates of bloodstream trypanosomes as well as midgut (for T. congolense and T. brucei) and epimastigote forms from infected Glossina morsitans centralis. There was no reactivity of the MoAbs with Theileria parva, Anaplasma marginale, Babesia bigemina or Plasmodium falciparum. These antibodies and the antigens they recognize should, therefore, prove useful in the development of assay systems for immunodiagnosis of African trypanosomiasis.